Application of electricity tracing theory and hybrid ant colony algorithm for ranking bus priority in power system - Hamid, Zulkiffli Abdul; Musirin, Ismail; Rahim, Muhammad Nor Azam; Kamari, Nor Azwan Mohamad (International journal of electrical power & energy systems, 2012)
► Stability index tracing technique has been proposed via optimization technique. ► The technique is applicable for any countermeasures concerning voltage stability. ► The proposed technique requires no assumption and provide reliable ranking list. ► Hybrid ant colony algorithm is proposed for fast and reliable optimization. Locating the most suitable locations in power system for any corrective and preventive actions is not an easy task especially for large scale network. The recent methods for determining the suitable generators for power scheduling and locations for shunt elements placement such as capacitor bank and Flexible Alternating Current Transmission System (FACTS) devices are sensitivity analysis, optimization approach, and stability index calculation. Meanwhile, there are also various power tracing techniques have been developed, but only applicable for transmission service pricing in deregulated environment. For a new approach, this paper proposes a technique to determine the suitability of locations in power system for any preventive and corrective actions via Fast Voltage Stability Index Tracing (FVSI-T) with the assistance of a new hybrid algorithm, Blended Crossover Continuous Ant Colony Optimization (BX-CACO). After experimentation and comparative studies, the proposed technique reflects a potential performance for real system applications.